Community, Spirituality, and the Writing Classroom - W. Keith Duffy (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
From a spiritual perspective, this article critiques the concept of community as defined by scholars of rhetoric and composition; the author suggests that our experience of community in the writing classroom cab be enhanced if we strike a balance between doing and being.